Modulation of expression of Connexins 37, 40 and 43 in endothelial cells in culture - Zhuang, Wenqing; Mitrou, Nick G. A.; Kulak, Steve; Cupples, William A.; Braam, Branko (Frontiers in Network Physiology, 2024)
Connexin (Cx) 37, 40 and 43 are implicated in vascular function, specifically in electrical coupling of endothelial cells and vascular smooth muscle cells. In the present study, we investigated whether factors implicated in vascular dysfunction can modulate gene expression of Cx37, Cx40 and Cx43 and whether this is associated with changes on endothelial layer barrier function in human microvascular endothelial cells (HMEC1). First, HMEC1 were subjected to stimuli for 4 and 8 hours. We tested responses to DETA-NONOate, H2O2, high glucose and angiotensin II, none of which relevantly affected transcription of the connexin genes. Next, we tested inflammatory factors IL-6, IFNg, and TNFa. IFNg (10 ng/ml) consistently induced Cx40 expression at 4h and 8h to 10-20-fold when corrected for the control. TNFa and IL6 resulted in small but significant depressions of Cx37 expression at 4h. Two JAK inhibitors, EGCG (100-250 µM) and AG490 (100-250 µM) dose-dependently inhibited the induction of Cx40 expression by IFNg.Subsequently, HMEC1 was subjected to 10 ng/ml IFNg for 60h and intercellular and transcellular impedance was monitored by Electric Cell-substrate Impedance Sensing (ECIS). In response to IFNg, junctional-barrier impedance increased more than cellular-barrier impedance; this was prevented by AG490 (5 µM). In conclusion, IFNg can strongly induce Cx40 expression and modify the barrier properties of the endothelial cell membrane through the JAK/Stat pathway. Moreover, Cx37, Cx40 and Cx43 expression in endothelial cells is stable, and, apart from IFNg, not affected by a number of factors implicated in endothelial dysfunction and vascular disease.